(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Background: Postmortem artifacts are any changes caused or features introduced in a body after death that may lead to misinterpretation of findings. Forensic experts should have adequate knowledge about artifacts that are introduced/produced in the dead body due to the autopsy procedure. It is important to report and note down features that are added due to the first medicolegal autopsy and which can be misinterpreted during further observations or the second autopsy, leading to untoward complications. Case Presentations: We hereby report the phenomenon of post-autopsy production of subperiosteal hemorrhages, its probable causes, and likely ways to prevent the same. This is a case series, reporting pre and post-opening observations of calvaria in 05 cases, brought for medicolegal autopsy. In all 05 cases, subperiosteal hemorrhages were noted in the opened calvaria along postmortem fracture lines in dependent positions when a repeat examination was done after the completion of the autopsy just before the commencement of suturing.